The Influence of Organizational Culture and Motivation on the Performance of Employee Students in the Bogor Region - Putri Azzahra Kurniawan; Hilda Melinia Safitry; Triyuli Kumala (Formosa Journal of Science and Technology, 2022)
Organizational culture has indeed become a pattern of basic assumptions that are determined or developed by a group of people in a company where the place for learning to overcome problems of external adaptation and internal integration has worked so well that it is considered legitimate to be taught to new members as the right way to think. This will affect employee motivation towards the work they are currently doing and affect the performance of the form of accountability to the organization and the public. Performance in carrying out its functions does not stand alone, but is always related to employee job satisfaction and the level of compensation given, and is influenced by skills, abilities and individual characteristics. Therefore the research aims to determine how much influence organizational culture and motivation have on employee performance and this research uses quantitative data on questionnaire distribution by obtaining a total of 101 samples of respondents and using the t test, f test and the coefficient of determination test.